2022
DOI: 10.1097/rlu.0000000000004307
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Patient With Metastatic Gastrointestinal Neuroendocrine Tumor and Meningioma Submitted to Peptide Receptor Radionuclide Therapy With 177Lu-DOTATATE

Abstract: A 76-year-old woman affected by pancreatic neuroendocrine tumor previously subjected to surgery with progressive liver disease and a concomitant mild symptomatic meningioma of the left pontocerebellar angle underwent 4 cycles of peptide receptor radionuclide therapy with 177 Lu-DOTATATE. A prophylactic therapy with corticosteroids was carried out before each treatment cycle, and the neurosurgery unit was alerted in case of cerebral edema and related neurologic symptoms. A 68 Ga-DOTATOC PET/CT scan performed af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…4 For instance, it has been demonstrated that in anatomically complex regions such as the skull base, SSTR PET provides valuable additional information for the differential diagnosis of meningioma. 2,3,[5][6][7][8][9][10][11] On the other hand, reports on the clinical value of SSTR PET for the differential diagnosis of lesions located at intracranial brain vessels such as sinuses remain scarce. DOTATATE PET revealed pathologically increased uptake in the patient presented, with an SUV of 4.9 in the lesion located within the superior sagittal sinus (green arrow, D), indicating a falcine meningioma.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…4 For instance, it has been demonstrated that in anatomically complex regions such as the skull base, SSTR PET provides valuable additional information for the differential diagnosis of meningioma. 2,3,[5][6][7][8][9][10][11] On the other hand, reports on the clinical value of SSTR PET for the differential diagnosis of lesions located at intracranial brain vessels such as sinuses remain scarce. DOTATATE PET revealed pathologically increased uptake in the patient presented, with an SUV of 4.9 in the lesion located within the superior sagittal sinus (green arrow, D), indicating a falcine meningioma.…”
Section: Figurementioning
confidence: 99%
“…The particular value of SSTR PET for differential diagnosis of meningiomas was highlighted in several studies and by the RANO (Response Assessment in Neuro-Oncology) working group 4 . For instance, it has been demonstrated that in anatomically complex regions such as the skull base, SSTR PET provides valuable additional information for the differential diagnosis of meningioma 2,3,5–11 . On the other hand, reports on the clinical value of SSTR PET for the differential diagnosis of lesions located at intracranial brain vessels such as sinuses remain scarce.…”
mentioning
confidence: 99%
“…While five-year survival rate for grade I exceeds 80%, it is poorer for malignant and atypical meningiomas at less than 60% (Marosi et al 2008 ). Treatment is usually surgical when localized and radiotherapy in more widespread lesions, while peptide receptor radionuclide therapy (PRRT) could achieve stable disease in up to 66.6% (Filippi et al 2022 ; Pirisino et al 2022 ). Although seen as gold standard in grade III, radiotherapy is debated for grade II and generally not indicated for grade I when resectable (Maggio et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%